The blue economy 3.0 the marriage of science, innovation and entrepreneurship creates a new business model that transforms society - Pauli, Gunter A. (Xlibris, 2017)
The Blue Economy cites a new business model in China where novel paper production turns crushed rocks, including mining waste that has piled up over centuries into sheets for printing, writing and packaging without the use of water, without cutting down a tree, and recyclable forever. It details how thistles, considered a weed, is turned into a plastic, a lubricant and a herbicide converting an old petrochemical plant into a biorefinery